Multiple criteria decision making in application layer networks - Frank Schneider (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2008)
This work is concerned with the conduct of MCDM by intelligent agents trading commodities in ALNs. These agents consider trustworthiness in their course of negotiation and select offers with respect to product price and seller reputation.
urn:nbn:de:bvb:703-opus-4573
Keywords: 380; Grid Computing